1999
DOI: 10.1046/j.1365-2222.1999.00501.x
|View full text |Cite
|
Sign up to set email alerts
|

Nedocromil sodium eye drops are more effective than sodium cromoglycate eye drops for the long‐term management of vernal keratoconjunctivitis

Abstract: Nedocromil sodium 2% eye drops is significantly more effective than sodium cromoglycate for treatment of VKC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
44
0
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(45 citation statements)
references
References 35 publications
0
44
0
1
Order By: Relevance
“…In earlier comparative studies of medications for patients with VKC, the longest treatment period was 5 months reported by Verin et al [6]. In this study, two mast cell-stabilizing agents, nedocromil sodium and sodium cromoglycate, were compared, and nedocromil sodium 2% eye drops were significantly more effective than sodium cromoglycate for the treatment of limbal type VKC.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In earlier comparative studies of medications for patients with VKC, the longest treatment period was 5 months reported by Verin et al [6]. In this study, two mast cell-stabilizing agents, nedocromil sodium and sodium cromoglycate, were compared, and nedocromil sodium 2% eye drops were significantly more effective than sodium cromoglycate for the treatment of limbal type VKC.…”
Section: Discussionmentioning
confidence: 99%
“…Although most cases of allergic conjunctivitis that belongs to the mild spectrum of allergic conjunctival diseases can be controlled by local mast cell-stabilizing anti-allergic drugs, it is difficult to maintain patients with VKC only with anti-allergic eye drops without the concomitant use of corticosteroids [6]. Therefore, topical corticosteroids remain the mainstay of therapy for bringing VKC under control.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The enzymatic reaction was started by adding 100 µl of clear supernatant in a spectrophotometric cuvette containing 800 µl of 0.3 mM reduced nicotinamide adenine dinucleotide phosphate (NADPH), 100 µl of 6 mM 5,5-dithiobis-2-nitrobenzoic acid (DTNB) and 10 µl of 50 units/ml GSH reductase Nedocromil sodium (NDS) and sodium cromoglycate (SCG) are mast cell stabilizers that are widely used as prophylactic agents in the treatment of bronchial asthma. Pharmacological studies have demonstrated that NDS is a more potent (Verin et al, 1999;Spezia et al, 1993;Lal et al, 1993) or at least equally effective (Kelly et al, 2001;Robuschi et al, 1997;De Benedictis et al, 1995) as the progenitor of SCG. The benefi cial effects of SCG in gastrointestinal injury have been reported in experimental (Ali, 1995;Beck et al, 1989;Ogle and Hui, 1995;Goossens et al, 1987) and clinical (Di Gioacchino et al, 1990;Moots et al, 1988;Grace et al, 1987;Caporali et al, 1986) studies, whereas the gastroprotective activity of NDS remains to be explored.…”
Section: Determination Of Glutathione (Gsh)mentioning
confidence: 98%
“…Despite its benign and self-limited presentation, therapeutic procedures are required to control signs and symptoms of the disease and to prevent the permanent inflammatory sequelae that may lead to fibrovascular reaction, new collagen deposition, tissue remodeling and permanent visual damage [5][6][7]. Despite some therapeutic options, it is difficult in most cases to maintain the patients' improvements without the use of corticosteroids [8]. However, prolonged use of steroid eye drops may result in serious problems such as cataracts, secondary infection and ocular hypertension [9][10][11].…”
Section: Introductionmentioning
confidence: 99%